A global meta-analysis of heavy metal(loid)s pollution in soils near copper mines: Evaluation of pollution level and probabilistic health risks - Chen, Li; Zhou, Mingxi; Wang, Jingzhe; Zhang, Zhiqin; Duan, Chengjiao; Wang, Xiangxiang; Zhao, Shuling; Bai, Xiaohan; Li, Zhijie; Li, Zimin; Fang, Linchuan (The Science of the total environment, 2022)
With the rapid development of the mining industry, the pollution of heavy metal(loid)s in soils near copper (Cu) mining sites is a significant concern worldwide. However, the pollution status and probabilistic health risks of heavy metal(loid)s of soils associated with Cu mines, have rarely been studied on a global scale. In this study, eight heavy metal(loid) concentrations in soil samples taken near 102 Cu mining sites worldwide were obtained through a literature review. Based on this database, the heavy metal(loid) pollution and ecological risk in soils near Cu mines were evaluated. Most of the study sites exceeded the moderately to heavily polluted levels of Cu and Cd; compared to other regions, higher pollution levels were observed at sites in Oman, China, Australia, and the United Kingdom. Soil pollution by Cd, Pb, and Zn at agricultural sites was higher than that in non-agricultural sites. In addition, these heavy metal(loid)s produced a high ecological risk to soils around Cu mining sites in which the contribution of Cd, Cu, and As reached up to 46.5%, 21.7%, and 18.4%, respectively. The mean hazard indices of the eight heavy metal(loid)s were 0.209 and 0.979 for adults and children, respectively. The Monte Carlo simulation further predicted that 1.40% and 29.9% of non-carcinogenic risk values for adults and children, respectively, exceeded the safe level of 1.0. Moreover, 84.5% and 91.0% of the total cancer risk values for adults and children, respectively, exceeded the threshold of 1E-04. Arsenic was the main contributor to non-carcinogenic risk, while Cu had the highest exceedance of carcinogenic risk. Our findings indicate that the control of Cu, Cd, and As should be prioritized because of their high incidence and significant risks in soils near Cu mines. These results provide valuable inputs for policymakers in designing effective strategies for reducing the exposure of heavy metal(loid)s in this area worldwide.
Keywords: dospělí; A global scale; hodnocení rizik; dítě; kadmium; Health risk assessment; Adult; Soil Pollutants; China; monitorování životního prostředí; Cadmium; látky znečišťující půdu; znečištění životního prostředí; lidé; Monte Carlo simulation; Risk Assessment; Environmental Pollution; měď; Cu mining sites; Copper; Ecological risk; těžké kovy; Environmental Monitoring; Čína; Child; Soil; půda; Metals, Heavy; Pollution status; Humans